2012
DOI: 10.1155/2012/379569
|View full text |Cite
|
Sign up to set email alerts
|

Drug Discovery Models and Toxicity Testing Using Embryonic and Induced Pluripotent Stem-Cell-Derived Cardiac and Neuronal Cells

Abstract: Development of induced pluripotent stem cells (iPSCs) using forced expression of specific sets of transcription factors has changed the field of stem cell research extensively. Two important limitations for research application of embryonic stem cells (ESCs), namely, ethical and immunological issues, can be circumvented using iPSCs. Since the development of first iPSCs, tremendous effort has been directed to the development of methods to increase the efficiency of the process and to reduce the extent of genomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 86 publications
0
18
0
3
Order By: Relevance
“…Thus, IPSC technology is increasingly being explored to analyze and predict adverse drug reactions in the liver, heart or neurons. While such systems have been successfully developed for humans222324 and are the focus of intensive validation25, similar models for NHPs are still lacking. However, due to the increasing complexity and species-specificity of novel drugs, such as therapeutic antibodies or RNA therapeutics (e.g., ASOs, siRNA), there is an increasing need to use NHPs for in vivo studies, which implies an increased need for predictive NHP in vitro systems.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, IPSC technology is increasingly being explored to analyze and predict adverse drug reactions in the liver, heart or neurons. While such systems have been successfully developed for humans222324 and are the focus of intensive validation25, similar models for NHPs are still lacking. However, due to the increasing complexity and species-specificity of novel drugs, such as therapeutic antibodies or RNA therapeutics (e.g., ASOs, siRNA), there is an increasing need to use NHPs for in vivo studies, which implies an increased need for predictive NHP in vitro systems.…”
Section: Discussionmentioning
confidence: 99%
“…It is demonstrated that iPSCs are currently being used for high-throughput screening and chronic toxicity assessment of cardiac, hepatic, and nervous tissues [29]. Recent report by Deshmukh et al [30] describes that ES cells and iPSCs are efficiently used to screen cardiac and neurotoxic agents. iPSCs derived from different somatic cells may be used to produce unrepaired somatic cells for disease modeling or drug screening (Fig.…”
Section: Tripathy and Mohantymentioning
confidence: 99%
“…In an early study of a human neural stem cell line derived from umbilical cord blood, several stages of neural commitment and differentiation were established and less differentiated cells were shown to be more sensitive to neurotoxins (Buzanska et al 2009 ). Changes in intracellular calcium may also provide a useful indication of neurotoxicity, offering an alternative to PC12 cells and other immortalized cell lines that display a partial neuronal phenotype and/or are derived from non-human species (Deshmukh et al 2012 ). With these encouraging developments, the next challenge is to standardize protocols for neurotoxicology testing with iPSC derived progenitors and differentiated cells.…”
Section: Neurotoxicity Screeningmentioning
confidence: 99%